الشروط الجعلية ودورها في استمرارية عقد الزواج - معروف أشواق  طابي حنان (جامعة المسيلة, 2021)
ملخص البحث إن موضوع الاشتراط في عقد الزواج يلقى اهتماما كبيرا وتطورا ملحوظا، فدراسة هذا الموضوع لينة باعتباره فقهيا قانونيا وواقعيا، وبالتالي قمنا بدراسة موضوع الاشتراط في عقد الزواج من الناحية الفقهية والقانونية كذلك تناوله من الجانب التطبيقي عبر إدراج قرارات المحكمة العليا التي تعرضت لهذا الموضوع، مع توضيح الاختلاف بين الآراء الفقهية التي منها ما كان مضيقا إذ ذهبوا أن الأصل في الاشتراط المنع إلا إذا دل نص على إباحته، وموسع فالأصل من الاشتراط عندهم الاباحة إلا اذا قام دليل على منعه، ايضا تجلى دور قانون الأسرة في وضع ضوابط وقيود لحرية الاشتراط ، مع إبراز دور الاشتراط في استمرار عقد الزواج وعلاقتها بمبدأ سلطان الإرادة ثم دور القاضي في موازنة العقد، وفي الأخير دراسة الآثار المختلفة للاشتراط من الناحية الفقهية والقانونية. الكلمات المفتاحية: الشروط الجعلية، الأسرة، الحماية القانونية، الاشتراط، عقد الزواج. Research The subject of requirement in marriage contract has developed and is witnessing a great interest recently. Studying this subject could be flexible considering that it is realistically legal and jurisprudential. Therefore, this work aims at studying the requirement in marriage contract from legal and jurisprudential aspect. Also, the practical aspect is included by providing Supreme Court decisions that dealt with this subject. The differences between jurisprudential views have been discussed, since some were very narrowing. Some suggested that prevention in the requirement is what should be done, unless there was a text that advocated its legalisation. Others believed that things should be done the other way round. In addition, the family law played an important role at establishing controls and restrains to the requirement freedom. Similarly, a great focus is given to the role of requirement in the continuity of marriage contract, its relationship to the ruler and the judge at main‏taining the balance in the contract. At last, the study attempts to demonstrate the different implications of the requirement from legal and jurisprudential aspect. Key words Marriage Contract, Family, The Legal Protection, Imperative conditions.
Keywords: الشروط الجعلية، الأسرة، الحماية القانونية، الاشتراط، عقد الزواج.